Spatiotemporal Distribution and Assemblages of Planktonic Fungi in the Coastal Waters of the Bohai Sea - Wang, Yaqiong; Sen, Biswarup; He, Yaodong; Xie, Ningdong; Wang, Guangyi (Frontiers in Microbiology, 2018)
Fungi play a critical role in the nutrient cycling and ecological function in terrestrial and freshwater ecosystems. Yet, many ecological aspects of their counterparts in coastal ecosystems remain largely elusive. Using high-throughput sequencing, quantitative PCR, and environmental data analyses, we studied the spatiotemporal changes in the abundance and diversity of planktonic fungi and their abiotic and biotic interactions in the coastal waters of three transects along the Bohai Sea. A total of 4362 ITS OTUs were identified and more than 60% of which were unclassified Fungi. Of the classified OTUs three major fungal phyla, Ascomycota, Basidiomycota, and Chytridiomycota were predominant with episodic low dominance phyla Cryptomycota and Mucoromycota (Mortierellales). The estimated average Fungi-specific 18S rRNA gene qPCR abundances varied within 4.28×106 and 1.13×107copies/L with significantly (P<0.05) different abundances among the transects suggesting potential influence of the different riverine inputs. The spatiotemporal changes in the OTU abundance of Ascomycota and Basidiomycota phyla coincided significantly (P<0.05) with nutrients traced to riverine inputs and phytoplankton detritus. Among the eight major fungal orders, the abundance of Hypocreales varied significantly (P<0.01) across months while Capnodiales, Pleosporales, Eurotiales, and Sporidiobolales varied significantly (P<0.05) across transects. In addition, our results likely suggest a tripartite interaction model for the association within members of Cryptomycota (hyperparasites), Chytridiomycota (both parasites and saprotrophs), and phytoplankton in the coastal waters. The fungal network featured several hubs and keystone OTUs besides the display of cooperative and competitive relationship within OTUs. These results support the notion that planktonic fungi, hitherto mostly undescribed, play diverse ecological roles in marine habitats and further outline niche processes, tripartite and co-occurrence interaction as the major drivers of their community structure and spatiotemporal distribution in the coastal water column.